Décompression endoscopique du nerf ulnaire dans le syndrome cubital au coude: à propos de 55 patients - Leclère, Franck Marie Patrick; Manz, S.; Unglaub, Frank; Cardenas, E.; Hahn, Peter (Neurochirurgie, 2011)
Introduction - Sulcus ulnaris syndrome is the second most common neurocompression syndrome in the upper limb after carpal tunnel syndrome. Its severity can be appreciated by the Dellon Classification. We present our experience and results after endoscopic decompression. - Patients and methods - A retrospective chart review of 55 patients operated over a 3-year period was performed. The patients, 37 men and 18 women, had an average age of 54years (range: 27-82years) at the time of surgery. The clinical diagnostic was always confirmed by a neurophysiological examination of the nerve conduction. According to the Dellon Classification, 11 patients had mild sulcus ulnaris syndrome, 31 had moderate and 13 had severe. The mean follow-up time was 21months (range: 6-42months). - Results - The sensibility was normalised in 85% of the patients. Compared to the contralateral non-operated side, the mean grip strength improved from 68 to 94% and the mean pinch grip from 72 to 95%. The rate of nerve luxation did not change (5.5%). According to the modified Bishop rating system, 38 patients (69%) had excellent, 13 patients (23.5%) good and four patients (7.5%) fair results. One haematoma necessitating a revision, a minimal lesion of the ulnar nerve with restitution ad integrum and a hypoesthesia of the elbow, occurred after surgery resulting in a complication rate of 5.5%. Ninety-eight percent of the patients responded that they would undergo the endoscopic procedure again if needed. - Conclusion - Endoscopic decompression of the ulnar nerve in sulcus ulnaris syndrome is very well appreciated by patients and also provides promising clinical results. - Résumé - Introduction - Le syndrome ulnaire au coude est, après le syndrome du canal carpien, le deuxième des syndromes de compression nerveuse au membre supérieur. Sa sévérité peut être appréciée par la classification de Dellon. Nous présentons notre expérience et nos résultats à propos de sa décompression endoscopique. - Patients et méthodes - L’étude rétrospective concerne 55 patients, 37 hommes et 18 femmes, sur une période de trois ans. L’âge moyen est de 54ans au moment de l’opération (extrêmes de 27 à 82ans). Le diagnostic clinique est toujours confirmé par un examen neurophysiologique de mesure des vitesses de conduction nerveuse. Parmi les patients, 11 sont de stade Dellon I, 31 de stade II et 13 de stade III. Le recul moyen est de 21 mois (extrêmes de six à 42 mois). - Résultat - Chez 85 % des patients, l’opération permet une normalisation de la sensibilité. Comparée au côté controlatéral non opéré, la force moyenne de préhension passe de 68 à 94 % et la force moyenne de la pince pouce-index de 72 à 95 %. Le taux de subluxation du nerf reste constant (5,5 %). Appréciés selon le score de Bishop modifié, les résultats sont excellents dans 38 cas (69 %), bons dans 13 cas (23,5 %) et moyens dans quatre cas (7,5 %). Un hématome sous-cutané nécessitant une révision, une lésion partielle du nerf ulnaire avec restitution ad integrum lors de la mise au point de la technique et une hypoesthésie postopératoire du coude portent le taux des complications à 5,5 %. Quatre-vingt-dix-huit pour cent des patients déclarent qu’ils se feraient de nouveau opérer par cette méthode si le choix leur était à nouveau proposé. - Conclusion - La décompression endoscopique du nerf ulnaire au coude est une méthode très appréciée par les patients pour le traitement de la compression cubitale au coude. Ses résultats cliniques semblent prometteurs.
Gesehen am 08.08.2022